2020
DOI: 10.2967/jnumed.120.250977
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Modeling of 18F-(2S,4R)4-Fluoroglutamine in Mouse Models of Breast Cancer to Estimate Glutamine Pool Size as an Indicator of Tumor Glutamine Metabolism

Abstract: The PET radiotracer 18 F-(2S,4R)4-Fluoroglutamine ( 18 F-Gln) reflects glutamine transport and can be used to infer glutamine metabolism. Mouse xenograft studies have demonstrated that 18 F-Gln uptake correlates directly with glutamine pool size and is inversely related to glutamine metabolism through the glutaminase enzyme. To provide a framework for the analysis of 18 F-Gln-PET, we have examined 18 F-Gln uptake kinetics in mouse models of breast cancer at baseline and after inhibition of glutaminase. We desc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 36 publications
4
22
0
Order By: Relevance
“…Previous studies suggested that [ 18 F]4-FGln labels the intracellular Gln pool and, indirectly, is a glutaminolytic marker (8). This was recently supported by a kinetic analysis applied on murine breast cancer models (21) and confirmed here by the demonstration that [ 18 F]4-FGln uptake in JJN3 tumors is described by a one-compartment, reversible tissue model with no trapping. Thus, [ 18 F]4-FGln proves a dynamic tool for research and potential clinical use in MM.…”
Section: F]fdg In Extramedullary Lesion Insupporting
confidence: 83%
See 3 more Smart Citations
“…Previous studies suggested that [ 18 F]4-FGln labels the intracellular Gln pool and, indirectly, is a glutaminolytic marker (8). This was recently supported by a kinetic analysis applied on murine breast cancer models (21) and confirmed here by the demonstration that [ 18 F]4-FGln uptake in JJN3 tumors is described by a one-compartment, reversible tissue model with no trapping. Thus, [ 18 F]4-FGln proves a dynamic tool for research and potential clinical use in MM.…”
Section: F]fdg In Extramedullary Lesion Insupporting
confidence: 83%
“…In tumor, [ 18 F]4-FGln uptake peaked at 25 min slowly declining thereafter (Figure 2B). The Logan plot (Figure 2C) confirmed linearity starting at 15 min from injection, consistent with largely reversible tracer exchange (21). The R 2 value for the fits of data from JJN3-grafted mice was 0.9989.…”
Section: Tumor and Muscle Time Activity Curves Of [ 18 F]4-fglnsupporting
confidence: 61%
See 2 more Smart Citations
“…Sensitivity curves were calculated as percent change in model output corresponding to 1% change in each parameter. Repeatability of kinetic parameter estimation was analyzed using simulated data based on ranges of individual kinetic parameters via methods of Viswanath et al (14). Bias was averaged across each of 100 noise realizations, and averaged across 200 runs.…”
Section: Kinetic Model Performancementioning
confidence: 99%